2017
DOI: 10.1080/0966369x.2017.1298572
|View full text |Cite
|
Sign up to set email alerts
|

The legal grading of sexual citizenship: sentencing practices in Norwegian rape cases

Abstract: This article maps and discusses the legal processing of rape cases in Norwegian appellate courts. Drawing on data from a multivariate regression analysis and a qualitative frame analysis, we examine the significance of space, accuser-convict prior relationship, the social context, accuser-convict marital relationship status, and convict racial background for grading of sentences in rape cases. The dataset consists of 176 rape cases that were processed in 2011 and 2012. Excluding acquittals and controlling for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Legal practice is fundamentally concerned with negotiation and assessment of narratives (Kjus 2005), which involves perspectivetaking and human capability for sympathy and compassion among judges, prosecutors, and defense lawyers alike. 9 As I note above, the quantitative study of sentencing practice in rape cases preceding this study found that lenient sentencing was practiced without reference to law in a number of cases (Bitsch and Klemetsen 2017). In line with the existing research, the overall pattern in the study of Norwegian sentencing practice confirms that racial and gender bias affects sentencing practice.…”
Section: Methods and Datasupporting
confidence: 77%
See 4 more Smart Citations
“…Legal practice is fundamentally concerned with negotiation and assessment of narratives (Kjus 2005), which involves perspectivetaking and human capability for sympathy and compassion among judges, prosecutors, and defense lawyers alike. 9 As I note above, the quantitative study of sentencing practice in rape cases preceding this study found that lenient sentencing was practiced without reference to law in a number of cases (Bitsch and Klemetsen 2017). In line with the existing research, the overall pattern in the study of Norwegian sentencing practice confirms that racial and gender bias affects sentencing practice.…”
Section: Methods and Datasupporting
confidence: 77%
“…In the dataset, and as illustrated by the example in the analysis above, majority men might be found guilty because their actions were violating the law; that is, they were not justified, but courts were to some extent willing to excuse them, in particular in cases that do not match the "real rape" stereotype. As verified by the quantitative study, majority men averagely receive 20 percent lighter sentences than do minority men (Bitsch and Klemetsen 2017).…”
Section: White Guilt Black Shamementioning
confidence: 60%
See 3 more Smart Citations